Virome bioprospection in ornamental plants of Bromeliaceae and Orchidaceae families in brazilian highlands - Silva, Juliana Gabrielle Isidorio da (2023)
Dissertação (mestrado) — Universidade de Brasília, Instituto de Ciências Biológicas, Departamento de Fitopatologia, 2023.